DINAMIKA POLITIK DAN HUKUM DESENTRALISASI ASIMETRIS DI INDONESIA - Putra, Ridwan; Suryanti, Rini; Chynta, Delfia; Putri, Berliana; Nabilla, Mutasya Lifa (Ensiklopedia of Journal, 2024)
Abtract: Indonesia has implemented various forms of asymmetrical decentralization from colonial times to the present era of reform. As for the legal basis for implementing asymmetric decentralization in Indonesia, there are several laws. One of them is NRI 1945 UUD Article 18B and Act No. 32 of 2004 on Regional Governance. In this study, the method of approach used is normative jurisprudence. Based on the results of research and discussion it can be concluded that the first application of asymmetric decentralization in Indonesia has had a significant impact on the regulatory disharmony between the central government and the special district can also have an impact on development coordination nationally. Political overlap and legal disharmony could hinder the synergy and integration of government programmes across the Indonesian territory. Second In the context of asymmetric decentralization, the provinces of Aceh, Papua, and West Papua receive special autonomy funds from the central government, while the province of Yogyakarta receives Special Funds. The three political dynamics versus asymmetric decentralization are also seen in competition between regions with special status, where each region struggles for interests and rights in particular, resulting in the issue of centralization versus decentralisation in central and complex regional relations.Keywords: dynamics, politics & law, asymmetric decentralization.